1999
DOI: 10.1111/j.1551-2916.1999.tb20075.x
|View full text |Cite
|
Sign up to set email alerts
|

High‐Temperature Oxidation of Boron Nitride: I, Monolithic Boron Nitride

Abstract: High‐temperature oxidation of monolithic boron nitride (BN) is examined at 900–1200°C. Hot‐pressed BN and both low‐ and high‐density chemically vapor‐deposited BN are studied. The oxidation product is B2O3(l) and the oxidation kinetics are sensitive to crystallographic orientation, porosity, and impurity levels. The B2O3 product also reacts readily with ambient water vapor in the test furnace (ppm levels) to form the volatile species HBO2(g), leading to overall paralinear kinetics. The linear rate constant ext… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
147
0

Year Published

2000
2000
2014
2014

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 172 publications
(154 citation statements)
references
References 18 publications
7
147
0
Order By: Relevance
“…Among these models, the paralinear kinetics model developed by Tedmon for Cr 2 O 3 -forming FeC alloys 13) has been widely adopted. For instance, Jacobson et al 9) and Opila 14) have applied the paralinear kinetics model to deal with the reaction kinetics of BN and SiC in wet oxygen and got a good agreement with the experimental data. However the paralinear kinetics model is not convenient to use because it is an implicit function.…”
Section: Introductionmentioning
confidence: 58%
See 2 more Smart Citations
“…Among these models, the paralinear kinetics model developed by Tedmon for Cr 2 O 3 -forming FeC alloys 13) has been widely adopted. For instance, Jacobson et al 9) and Opila 14) have applied the paralinear kinetics model to deal with the reaction kinetics of BN and SiC in wet oxygen and got a good agreement with the experimental data. However the paralinear kinetics model is not convenient to use because it is an implicit function.…”
Section: Introductionmentioning
confidence: 58%
“…Jacobson et al 9) also investigated the reaction behavior of CVD BN with density of 2.122.19 g/cm 3 in wet oxygen. The Guangwei et al: Reaction of CVD BN ceramics in water vapor at 1023-1173 K using different kinetic model ceramics was cut into the dimensions of approximately 3 cm © 1 cm © 1 cm and then cleaned.…”
Section: Results and Discussion 31 Reaction Behaviormentioning
confidence: 99%
See 1 more Smart Citation
“…4),5),7) It was also reported that the oxidation of BN was sensitive to water vapor due to the formation of volatile product, HBO 2 (g). 6) We have been examined a series of study on BN oxidation in dry oxygen and air (10 to 100÷ O 2 ), and in water vapor (5 to 20÷ H 2 O). 3), 7) In this paper, the oxidation kinetics of BN were investigated in wet oxygen at high temperatures (9001100 C) and compared to the oxidation kinetics in dry oxygen and water vapor.…”
Section: Introductionmentioning
confidence: 99%
“…The liquid delivery system and CVI reactor design used for coating deposition have been described in detail elsewhere [9]. For initial screening studies here, a smaller reactor with a 5 cm J.D.…”
Section: Methodsmentioning
confidence: 99%